Characterization of Chilean Higher Education Institutions (HEI): an approach towards a future model of university (Main reforms applied in the Latin-American higher education model that made an impact in the commercialization of the universities) - Carmona-López, Rafael Jaime (2014)
The research context that this article seeks to show the different models of college, from the evolution and development of universities and their management in Latin America, particularly in Chile, and how they affect the development of societies, both past and contemporary, highlighting some similar and different characteristics that they have. It should be noted that the Chilean model of education has been considered to have a great impact on some countries in Latin America, especially in Colombia. Moreover, the general objective of this research was the reflection on the reforms of higher education in Latin America and the impact these reforms have had in recent years in Chile, which seem to have created a high dissatisfaction in the social context, due to the excessive commercialization of educational services.  For the development of this paper an extensive review of the literature, which accounts for the phenomenon to be investigated is made and semi-structured interviews were carried out to experts in the field, which helped to understand what authors explain in the literature concerning models and educational reforms in Latin America and the current situation of education in Chile, thereby achieving a clear vision of the reality of the problem.